2017
DOI: 10.1177/2047487317693131
|View full text |Cite
|
Sign up to set email alerts
|

Psychological mediators related to clinical outcome in cognitive behavioural therapy for coronary heart disease: A sub-analysis from the SUPRIM trial

Abstract: Background: The Secondary Prevention in Uppsala Primary Healthcare Project (SUPRIM) was a randomized controlled trial of a group-based cognitive behavioural therapy stress management programme for patients with coronary heart disease. The project was successful in reducing the risk of fatal or non-fatal first recurrent cardiovascular events. The aim of this study was to analyse the effect of cognitive behavioural therapy on self-rated stress, somatic anxiety, vital exhaustion and depression and to study the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Although anxiety disorders are as common in CAD patients as depressive disorders (unpublished data), research on their treatment is even scarcer ( 14 ). Panic disorder was successfully treated in CAD patients in the small PATCHD trial ( 15 ) and additional CBT reduced somatic anxiety in the SUPRIM trial ( 12 , 13 ). In addition, little is known about the utilization rates of mental health-care services by patients with CAD and comorbid affective or anxiety disorders, as well as about effectiveness of general mental health care in CAD patients outside of the research setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although anxiety disorders are as common in CAD patients as depressive disorders (unpublished data), research on their treatment is even scarcer ( 14 ). Panic disorder was successfully treated in CAD patients in the small PATCHD trial ( 15 ) and additional CBT reduced somatic anxiety in the SUPRIM trial ( 12 , 13 ). In addition, little is known about the utilization rates of mental health-care services by patients with CAD and comorbid affective or anxiety disorders, as well as about effectiveness of general mental health care in CAD patients outside of the research setting.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory processes are therefore unlikely as mediators between the CBT program and the positive results previously reported ( 7 ). It has also been shown that other measures—such as psychological outcomes, social support, physical activity, blood pressure, blood lipid levels, smoking, and use of secondary preventive medications or anti-depressants—were likewise unaffected by the treatment and therefore unlikely to explain the reduction in CV events and MIs ( 8 ). In order to explain the SUPRIM study’s main finding, the most important mechanisms are still to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome could not be explained by use of antihypertensives, lipid-lowering drugs, anti-depressants, or nicotine ( 7 ). Nor could it be explained by changes in stress behaviors, depression, or vital exhaustion ( 8 ). Only a minor positive effect of the program was found regarding somatic symptoms of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in coping with chronic illness and the complications associated with them, it has been shown that health monitoring and prognosis can significantly be improved with cognitive behavioural approaches (CBT) [12]. Combining mobile technologies with CBT for chronic patients can help those seeking treatment to improve their ability to cope with conditions [6]. Literature also suggests that mindfulness and other positive behavioural changes can be seen in patients that get mindfulness-based cognitive therapy (MBCT) [1].…”
Section: Background: Mhealth and Well-beingmentioning
confidence: 99%